Phosphorylation of the RNA-dependent protein kinase regulates its RNA-binding activity - V. Jammi, Narasimham (Oxford University Press, 2001)
The RNA-dependent protein kinase (PKR) is an interferon-induced, RNA-activated enzyme that phosphorylates the α-subunit of eukaryotic initiation factor 2 (eIF2α), inhibiting the function of the eIF2 complex and continued initiation of translation. When bound to an activating RNA and ATP, PKR undergoes autophosphorylation reactions at multiple serine and threonine residues. This autophosphorylation reaction stimulates the eIF2α kinase activity of PKR. The binding of certain viral RNAs inhibits the activation of PKR. Wild-type PKR is obtained as a highly phosphorylated protein when overexpressed in Escherichia coli. We report here that treatment of the isolated phosphoprotein with the catalytic subunit of protein phosphatase 1 dephosphorylates the enzyme. The in vitro autophosphorylation and eIF2α kinase activities of the dephosphorylated enzyme are stimulated by addition of RNA. Thus, inactivation by phosphatase treatment of autophosphorylated PKR obtained from overexpression in bacteria generates PKR in a form suitable for in vitro analysis of the RNA-induced activation mechanism. Furthermore, we used gel mobility shift assays, methidiumpropyl-EDTA·Fe footprinting and affinity chromatography to demonstrate differences in the RNA-binding properties of phospho- and dephosphoPKR. We found that dephosphorylation of PKR increases binding affinity of the enzyme for both kinase activating and inhibiting RNAs. These results are consistent with an activation mechanism that includes release of the activating RNA upon autophosphorylation of PKR prior to phosphorylation of eIF2α.